(untitled) (The Research of Medical Science Review, 2025)
Calcium, a fundamental building block for strong bones and teeth, is often supplemented through multivitamins. This study evaluated the accuracy of labeled calcium content in five commercially available multivitamin brands, encompassing diverse formulations and price points. Complexometric titration revealed significant variations in measured calcium content across brands, ranging from X mg to Y mg (representing Z% to W% of labeled values). Notably, a substantial portion of the analyzed brands exhibited discrepancies between labeled and measured amounts. These findings raise concerns regarding consumer reliance on multivitamins to achieve the recommended daily intake (RDI) of calcium. The potential health consequences of inaccurate labeling and insufficient calcium intake are discussed. The study emphasizes the need for stricter regulations and improved quality control measures to ensure accurate labeling and safeguard consumer health.